Pengaruh Harga Transfer, Ukuran Perusahaan dan Profitabilitas Terhadap Penghindaran Pajak Pada Perusahaan Sektor Energi Yang Terdaftar di BEI 2019 – 2022 - Sania Sania; Cahyadi Husadha; Elia Rossa (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2024)
This study aims to estimate and test the effect of Transfer Pricing, Company Size, and Profitability on Tax Avoidance. This research method uses quantitative research. The data used in this study is secondary data in the form of the company’s annual financial statements obtained through the official website of the Indonesia Stock Exchange. The sampling technique used is Purposive Sampling so that 18 companies can be obtained from 83 companies listed on the Indonesia Stock Exchange (IDX) and the number of observations is 72 data samples. Data processing in this research uses Eviews 12 software. The result of this research shows that transfer pricing has no effect on tax avoidance, company size has no effect on tax avoidance and probability has no effect on tax avoidance.